Innovation in teaching practices and development of digital competencies at Jean Jacques Rousseau University - Alemán Arróliga , Javier Antonio (Scientific journal of social studies, 2024)
This article examines the implementation of innovative teaching practices at Jean Jacques Rousseau University (UNIJJAR) to develop key digital competencies in students. Through a comparative analysis of successful cases at leading universities such as Stanford, Harvard, and Cambridge, methodologies such as project-based learning (PBL) and the flipped classroom are explored, highlighting their effectiveness in improving academic performance and digital literacy. The results suggest that integrating emerging technologies such as artificial intelligence and augmented reality can transform higher education, making it more interactive and personalized. The study also addresses a legal gap in Nicaraguan legislation related to the regulation of technology use in higher education, proposing pedagogical solutions. Significant challenges were identified, such as the need for investment in technological infrastructure and continuous teacher training. Creating a pedagogical innovation center at the university is recommended to lead the adoption of new technologies and educational methodologies, along with implementing a continuous evaluation system that allows teaching practices to be adjusted and optimized based on feedback from students and faculty. The effective application of these recommendations will prepare students for an increasingly digitalized and competitive job market.